Digital Architecture Planning Transformation Based on the Open Group Architecture Framework ADM - Wahyu Budianto; Surahman Surahman; Komaruddin Komaruddin; Teguh Yulianto (Syntax Corporation, 2023)
Companies need the role of Information Management Systems and Technology to provide convenience for Companies to transform data in an organized manner and implement the goals and objectives of their business strategy, namely increasing revenue, increasing reliability, reducing costs, and focusing on customers. PT XYZ, whose business processes are computerized but have yet to be optimal and integrated, has yet to be able to provide optimal support to improve the Company's performance. The standard method used in this analysis is to utilize Togaf ADM Frame. This research was conducted to produce an enterprise architecture plan through the steps in the Togaf ADM blueprint starting from Introduction, Management Requirements, Vision Design, Business Design, Information Management System Design, and Technology Design to Opportunities and Solutions. This study produces a System/IT blueprint that provides an enterprise architecture plan to address existing problems with a solution plan delivered on a modular framework, integrated systems, policy alignment, and service focus.